Unusual solid mass in the popliteal fossa. (8th May 2013) - Smurthwaite, Katharine Anne; Barnard, Edward
Abstract : We present a clinical case image of a 20-year-old man with a lump behind his knee. A radiograph taken in the emergency department demonstrated the classical appearance of an osteochondroma. Osteochondroma is the commonest skeletal neoplasm. Surgical excision results in symptom resolution in over 90% of patients.